The reliability of physical performance testing within elite adolescent pre-professional ballet dancers - Harding, J.; Tallent, J.; Sheriff, K.; McCann, C.; Cortes, N.; Olsson, L.; Shaw, J.; Howe, L. (Journal of Dance Medicine & Science, 2026)
Introduction: Evaluating and training strength qualities is crucial for the physical development of ballet dancers. Whilst data is available as to the sensitivity of strength tests for detecting changes in athlete populations, between-session reliability for adolescent ballet dancers is yet to be determined. This study aimed to determine the between-session reliability of physical performance tests in elite adolescent ballet dancers. Methods: Depending on the test, a cohort of 25 to 54 pre-professional ballet dancers (9 -30 males, 14-29 females) participated in a series of 6 physical tests across 12 sessions. Each testing session involved performing 1 strength test, with retesting administered 7 days later. The testing protocol included single-leg isometric squat, single-leg isometric plantarflexion, countermovement jump, standing single-leg countermovement jump, drop jump from 30 cm, and for males, seated overhead press to voluntary failure using 30 kg. Data was analyzed using a pairs sample t-test, interclass correlation coefficients and measures of absolute reliability including values of minimal detectable change. Results: Pairs sample t-tests revealed no systematic bias was present between trial 1 and 2 for each test. Across all tests, interclass correlation coefficients ranged from good to excellent (.89-.98), and coefficients of variation were 2.6% to 6.5%. Conclusion: These results indicate strength testing can reliably be integrated into a comprehensive physical performance testing battery to identify changes associated with improved physical performance across the academic year for adolescent ballet dancers. Based on the minimum detectable change values, changes in jump performance across the range of tests employed in this study can likely be detected after relatively short training periods. However, maximal isometric strength tests such as the single-leg squat may require longer than 6 weeks to detect performance changes. The current study expands the testing options for ballet training centers and high-performance settings, ensuring confidence in accurately measuring physical changes.